Strain-Specific Contribution of Eukaryotic Elongation Factor 1 Gamma to the Translation of Influenza A Virus Proteins - Shuhei Sammaibashi; Seiya Yamayoshi; Yoshihiro Kawaoka; Yoshihiro Kawaoka; Yoshihiro Kawaoka (Frontiers in Microbiology, 2018)
Influenza A virus exploits multiple host proteins during infection. To define the virus–host interactome, our group conducted a proteomics-based screen and identified 299 genes that contributed to virus replication and 24 genes that were antiviral. Of these genes, we focused on the role during virus replication of eukaryotic elongation factor 1 gamma (eEF1G), which is a subunit of the eukaryotic elongation factor-1 complex and known to be a pro-viral host protein. Using the CRISPR/Cas9 system, we obtained two clones that were defective in eEF1G expression. In both of these clones, A/WSN/33 (H1N1) virus growth and protein expression were significantly suppressed, but viral mRNA, vRNA, and cRNA expression were not reduced. However, the replication and protein expression of A/California/04/2009 (H1N1pdm) virus in both clones were similar to those in parental cells. We found that the PB2 and PA proteins of WSN virus were responsible for the eEF1G-dependent replication. Our data show that eEF1G plays a role in the translation of virus proteins in a strain-specific manner. Additional analyses may be needed to further understand the role of strain-specific host proteins during virus replication.